Entre esculpir e fissurar: a escritura da docência (Versión en portugués) - Tiago Martins de Morais (Ñawi: Arte, Diseño y Comunicación)
Filmmaker Andrei Tarkovski wrote he often wondered if it was worth writing about cinema. Wouldn't it be better just make films and find practical solutions to theoretical problems throughout the work? Although there was doubt, he bet on writing as a way to transform the plane of the ordinary where one acts in theme of investigation and, thus, capture, with the text, bulges in the perpetual flow of the real. In dialogue with Tarkovski, we can understand writing as a toll of attention to teaching – write about it, produce fiction about it and disturb the pedagogical thinking investing in a non-essentialized way, mobilizing, in writing, the marks and singularities of our pedagogical experiences. Aligned with Nietzsche's writing, a self- genealogical scripture is produced as an exercise, in a practice that is not restricted to an individual, but extends to a broader field of forces of which he or she belongs.